Trichostrongylus colubriformis extract upregulates TNF-α receptor expression and enhances TNF-α sensitivity of L929 cells - Riffkin, M.C.; Seow, H.-F.; Wood, P.R.; Brown, L.E. (Wiley, 2000)
Many pathogens have developed strategies to avoid the host's immune system and hence improve their long-term survival. These strategies include antigenic variation, mimicry of host regulatory proteins and production of immunoregulatory molecules. The ruminant gastrointestinal nematode Trichostrongylus colubriformis produces several factors with homology to human immunoregulatory proteins. However, direct immunomodulation by T. colubriformis proteins has not yet been unequivocally demonstrated. Results in the present paper demonstrate that soluble T. colubriformis factors promote proliferation of the TNF-susceptible mouse fibrosarcoma cell line L929, while inhibiting proliferation of all other cell types tested. In addition, T. colubriformis homogenate enhanced the susceptibility of L929 cells to the cytotoxic action of ovine TNF-α. Within 1 h of exposure, T. colubriformis factors bind L929 cells in a stable fashion, yet it takes up to 24 h for the cells to become sensitised to TNF-α. Interestingly, the increase of both TNF-α sensitivity and proliferation of treated L929 cells correlated with an upregulation in expression of TNF-α p55 and p75 receptors.